CONTEXTUAL THEOLOGY IMPLEMENTATION: BIBLICAL INTEGRATION WITH URBAN CHALLENGES IN INDONESIAN CITIES - Marlin, Marlin; Yando, Markus; Sihombing, Derma Watty (MAHABBAH: Journal of Religion and Education, 2023)
This qualitative research examines contextual theology implementation effectiveness in Bekasi and North Jakarta through comprehensive analysis of perspectives from pastors, theological educators, and church workers. The study employs semi-structured interviews with ten key stakeholders to assess current biblical integration approaches, identify gaps between theological knowledge and urban engagement, and develop evidence-based enhancement frameworks. Findings reveal strong biblical foundations alongside critical opportunities in community engagement programming, environmental stewardship, and interfaith collaboration. The research demonstrates substantial correlation between systematic contextual theology development and enhanced community relevance, social transformation impact, and Christian witness effectiveness. Community engagement programming emerges as the highest-impact improvement opportunity, while environmental stewardship initiatives and collaborative partnerships represent critical enhancement priorities. Results indicate exceptional readiness for coordinated development initiatives that leverage existing theological capacity while addressing contemporary urban challenges. The study contributes valuable insights regarding contextual theology implementation in Southeast Asian urban contexts while providing transferable frameworks for biblical integration with social challenges in diverse environments. Recommendations emphasize systematic community engagement establishment, interfaith partnership development, and institutional collaboration that enhances both theological relevance and practical community transformation effectiveness.